1983
DOI: 10.1152/jappl.1983.55.3.699
|View full text |Cite
|
Sign up to set email alerts
|

Renin-aldosterone and angiotensin-converting enzyme during prolonged altitude exposure

Abstract: The effect of 7 wk altitude exposure on plasma renin activity (PRA), plasma aldosterone concentration (PAC), and angiotensin-converting enzyme (ACE) activity was studied in 10 male subjects at 4,500 m. There was an initial increase in PRA and a reduction in PAC and ACE. The reduction in ACE was significantly greater in the four subjects who had frequently been exposed to extreme altitudes than in the other six subjects. These changes had returned to control values between 12 and 20 days. Exercise caused a mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 0 publications
4
21
0
Order By: Relevance
“…The statistical similarity of circulating ACE activity between the two groups may be further evidence of this difference when considering that ACE levels may be influenced by mountaineering and exposure to altitude. [24][25][26] We found that the I allelic frequency and I dominant genotypic distribution (II & ID) of ACE I/D polymorphism were significantly over-represented in the Sherpas compared to the non-Sherpas at low altitude, providing insight into the genetic background of these two groups. The prevalence of the I allele was commonly associated with low ACE activity in both groups irrespective of either ethnicity or altitude of residence.…”
Section: Genotypic Distributions and Allelic Frequencies Of The Ace Imentioning
confidence: 99%
“…The statistical similarity of circulating ACE activity between the two groups may be further evidence of this difference when considering that ACE levels may be influenced by mountaineering and exposure to altitude. [24][25][26] We found that the I allelic frequency and I dominant genotypic distribution (II & ID) of ACE I/D polymorphism were significantly over-represented in the Sherpas compared to the non-Sherpas at low altitude, providing insight into the genetic background of these two groups. The prevalence of the I allele was commonly associated with low ACE activity in both groups irrespective of either ethnicity or altitude of residence.…”
Section: Genotypic Distributions and Allelic Frequencies Of The Ace Imentioning
confidence: 99%
“…Any beneficial effect from low ACE associated with the I allele in terms of increased uncoupling of PRA and PAC may be short-lived, as the reduced PAC/PRA ratio seen at HA may normalize within 12-20 days (Milledge et al, 1983c). A subdued exercise response of PAC to PRA does persist (Milledge et al, 1983c), perhaps reflecting the down regulation of the AT1 receptor that is known to occur with sustained HA exposure (Jin et al, 1987, Chassagne et al, 2000.…”
Section: Woods and Montgomerymentioning
confidence: 99%
“…A subdued exercise response of PAC to PRA does persist (Milledge et al, 1983c), perhaps reflecting the down regulation of the AT1 receptor that is known to occur with sustained HA exposure (Jin et al, 1987, Chassagne et al, 2000. The down-regulation of AT1 receptors with chronic exposure may explain the apparent contradictory findings of a six-fold increase in II genotype frequency amongst subjects with high-altitude pulmonary hypertension in the Kyrghyz republic (Morrell et al, 1999).…”
Section: Woods and Montgomerymentioning
confidence: 99%
“…Most workers have demonstrated a reduction in plasma renin activity (PRA) at rest with HA exposure [1,[8][9][10][11][12]. In addition a reduced resting plasma aldosterone concentration (PAC) at HA has frequently been recorded [1,10,13,14]. A relatively greater drop in PAC to PRA increases the PRA:PAC ratio and reflects a reduced aldosterone response to renin.…”
Section: The Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%